Mediation of Job Satisfaction in the Analysis of the Influence of Work Culture, Work Motivation and Performance Allowances on Employee Performance - Sukiyono, Agus; Sumiyati, Siti (International Journal of Multidisciplinary Applied and Science Research, 2025)
This research aims to analyze the influence of work culture, work motivation and renumeration on employee performance. In addition, this research aims to analyze the influence of job satisfaction as an intervening variable between the relationship of work culture, work motivation and renumeration on employee performance. This research was conducted using a survey method by distributing questionnaires to research respondents. The respondents of this research are Civil Servants (PNS) in the SATPOL PP Demak District. The total sample used in this research was 70 employes. The analytical tool used in this research is IBM Statictics SPSS v.23. The results of this research indicate that work culture and work motivation have no effect on job satisfaction, while renumeration has a positive effect on job satisfaction. Work culture, work motivation and renumeration do not influence employee performance, while job satisfaction influences employee performance. As an intervening variable, job satisfaction is able to mediate the relationship between renumeration and employee performance. Meanwhile, the relationship between work culture and work motivation on employee performance cannot be mediated by job satisfaction.